Оцінка та облік витрат за міжнародними стандартами звітності - Ромашко, О.М. (Культура народов Причерноморья, 2013)
На сьогодні перед усіма суб’єктами господарювання постає проблема застосування
Міжнародних стандартів фінансової звітності. Оцінка статей звітності впливає безпосередньо на
правдивість інформації, що розкивається у звітності. Принцип оцінки широко використовується при
веденні бухгалтерського обліку та складанні фінансової звітності відповідно до міжнародних
стандартів. Одним із важливих показників діяльності підприємства, що має безпосередній вплив на
фінансовий результат є витрати. У статті розглянуто механізм визнання та оцінки витрат за
Міжнародними стандартами фінансової звітності. На сегодня перед всеми субъектами хозяйствования возникает проблема применения
Международных стандартов финансовой отчетности. Оценка статей отчетности влияет
непосредственно на правдивость информации, которая раскрывается в отчетности. Принцип оценки
широко используется при ведении бухгалтерского учета и составлении финансовой отчетности в
соответствии с международными стандартами. Одним из важных показателей деятельности
предприятия, который имеет непосредственное влияние на финансовый результат, являются
расходы. В статье рассмотрен механизм признания и оценки расходов в соответствии с
Международными стандартами финансовой отчетности. Relevance of the article is that today in front of all entities there is a problem of Adoption of
International Financial Reporting Standards. International Financial Reporting Standards are an effective tool
for improving the transparency and comprehensibility of information that reveal the activities of the entity,
create a reliable base for the recognition of costs allows objectively disclose the financial risks of the company.
International Financial Reporting Standards affect the quality of management decisions about the enterprise’s
activity and achieve positive results. Rating of reporting articles directly affects the veracity of the information
disclosed in reporting. The principle of assessment is widely used in accounting and preparation of financial
statements according to international standards. The priority is to assess the assets, basing on the cost of their
production and acquisition. Therefore, the costs are one of the important indicators of the company activity,
which have a direct impact on the financial result. The article reviews the mechanism of recognition and
measurement of costs according to the International Financial Reporting Standards. Moreover, the article
describes the benefits of IFRS in assessing the costs of the enterprise, the basic problems of the recognition and
measurement of certain expenses. In the article there is given comparison of existing national accounting
standards and International Financial Reporting Standards regarding measuring and recording reporting costs.
There are considered the features of prepaid expenses, progress, labor costs, cost of sales and services.